Feminist Collections, v.3, no.4 (summer 1982) - (:unkn) unknown (My University, 1982)
Subtitle: Women's Studies Library Resources in Wisconsin. 34p.
FROM THE EDITORS: A new Women's Studies Librarian-at-Large; Judy Gardner, Interim Women's Studies Librarian-at-Large reports on women's studies in the undergraduate library. ARCHIVES: The Lesbian and Gay Archives of Naiad Press. PAYING THEM THEIR DUE: WOMEN'S MUSIC IN THE LIBRARY: Polly Archer describes the women's music collection at Madison Public Library. WOMEN AND CRIMINAL JUSTICE: UW-Madison's Criminal Justice Reference and Information Center as a resource for the study of women and criminal justice, by Sue Center. FEMINIST PUBLISHING: Information on two new publishing houses. PERIODICAL NOTES: Three new periodicals: a political newsletter for women of Southeastern Wisconsin; a journal on women and therapy; and a British women's newspaper emphasizing news about black and Third World women. Special issues on: women's studies; contemporary women poets; women and work; women and medicine; women and the professions; the New Right; feminism and the Academy; and women and yoga. ITEMS OF NOTE: A new feminist mail order service, emphasizing books by and about women of color; a play about Wisconsin women's history; a slide show about comparable worth; correspondence courses in women's studies; a center for information about media relevant to women; and a "pathfinder" service for women's studies researchers. BOOK REVIEWS: A Rising Tide: A Review of Selected Books By and/or About Black Women, 1970-1981. Part 11: 1980-81, by Nellie McKay. Current Trends in the Study of Women in Jewish and Christian Religion: A Combined Review, by Rita M. Gross. SUPPLEMENT: FEMINIST COLLECTIONS INDEX: Vols. 1-3, 1980-1982.
Keywords: Women's Studies; Gender; Feminism; Library Resources; Reviews